Day case arthroscopy under local anaesthesia. - Wallace, D; Carr, A; Loach, AB; Wilson-MacDonald, J (1994)
A prospective study of the effectiveness of local anaesthesia in arthroscopy of the knee was performed in 212 consecutive patients. Arthroscopic surgery was undertaken successfully in 121 cases (57%), including meniscectomy and drilling of osteochondral defects. Dynamic evaluation of the patellofemoral joint articulation was possible and demonstration of pathological abnormalities was felt to be beneficial by some patients. The method described is safe, reliable, confers good postoperative analgesia and enables physiotherapy to begin immediately. Conversion to general anaesthesia was necessary in one case due to pain localised to a stiff and osteoarthritic hip. Intra-articular haemorrhage was found to be a problem in one case with synovitis. Only ten patients complained of moderate pain, none had severe pain. Local anaesthesia is contraindicated in cases with ipsilateral osteoarthritis of the hip or with significant synovitis of the knee. This technique is particularly suited to day case surgery.